VISUALIZING THE DATA VISUALIZATION NETWORK: THE DVMAP PROJECT - Rosário Durão; Tie Wei; Kristina Henneke; Karen M. Balch; Maxwell Hill; Rachel Rayl (European Scientific Journal, ESJ, 2014)
Data visualization is a familiar buzzword. Experts in the humanities, social and natural sciences, as well as technology, along with semi-experts and the general public, reach people everywhere with trends and conclusions drawn from visualized data. Governments, industries, businesses, sciences, marketers, academics, students and others value data visualization methods and tools as critical, applicable tools for understanding the world, which provide rich information analyses for specialists and generalists alike. Unfortunately, no single resource offers a space where people working in the multifaceted field of data visualization can share projects they are working on, tools they created, educational opportunities in the field, nor where they (and their work) are situated geographically. A research group at New Mexico Institute of Mining and Technology seeks to fill this gap with a repository of data visualization resources called ―Data Visualization Map (DVMap).‖ The DVMap is an interactive network data and geographic representation graph that provides a data visualization space for people across the world to share, view and/or collaborate on projects and publications; tools deployed or under development; educational opportunities in data visualization, such as formal programs, summer seminars, conferences; and the geographical locations of the users, projects, tools and educational opportunities. Given the necessity of this repository, this paper outlines the structure, underlying methodology, and anticipated outcomes for the DVMap data visualization network. The paper also accounts for limitations of the project and the potential problems of creating a map that wants to share work – especially work in progress – with everyone.